High‐Performance Organic Solar Cells Based on a Non‐Fullerene Acceptor with a Spiro Core. Issue 7 (7th February 2017) - Sun, Hua; Sun, Po; Zhang, Cong; Yang, Yingguo; Gao, Xingyu; Chen, Fei; Xu, Zongxiang; Chen, Zhi‐Kuan; Huang, Wei
Abstract: Derived from perylenediimide (PDI) building blocks, 3D PDI molecules are considered as a type of promising structure to overcome molecular aggregation, thus improving the performance of organic solar cells. Herein, we report a novel PDI‐based derivative, SCPDT‐PDI4, with four PDI units connected to a unique spiro core. Attributed to this novel molecular design, SCPDT‐PDI4 exhibits a rigid 3D structure, in which the aggregation tendency of PDI chromophores could be effectively attenuated. Additionally, strong intramolecular charge transfer and high charge mobility are achieved due to the well‐conjugated structure and electron‐rich property of SCPDT. Therefore, fullerene‐free organic solar cells based onSCPDT‐PDI4 and PTB7‐Th achieve a remarkable high efficiency of 7.11 %. Such an excellent result demonstrates the opportunity of SCPDT to be a promising building block for non‐fullerene acceptors. Abstract : Up the junction : Bulk heterojunction (BHJ) solar cells based on PTB7‐Th:SCPDT‐PDI4 with 2 % DIO additive show a high performance with a power conversion efficiency (PCE) up to 7.11 % (PTB7‐Th=poly[4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b;4, 5‐b′]dithiophene‐2, 6‐diyl‐ alt ‐(4‐(2‐ethylhexyl)‐3‐fluorothieno[3, 4‐b]thiophene‐)‐2‐carboxylate‐2‐6‐diyl)], SCPDT=4, 4′‐spirobi[cyclopenta[2, 1‐b;3, 4‐b′]dithiophene], PDI=perylenediimide, DIO=1, 8‐diiodooctane).